Biofilm Attached Cultivation of Chlorella pyrenoidosa Is a Developed System for Swine Wastewater Treatment and Lipid Production - Cheng, Pengfei; Wang, Yuanzhu; Liu, Tianzhong; Liu, Defu (Frontiers in Plant Science, 2017)
This study showed the new potential of using soluble contents and heavy metals in swine wastewater as nutrient supplements for the algae Chlorella Pyrenoidosa with biofilm attached method. Algae with biofilm attached cultivation grew well in unpasteurized wastewater reaching a biomass productivity of 5.03 gm-2d-1, lipid content of 35.9% and lipid productivity of 1.80 gm-2d-1. Chlorella grew in BG11 medium delivered lower values for each of the aforementioned parameters. The FAMEs compositions in the algae paste were mainly consisted of C16:0, C18:2, and C18:3. Algae removed NH4+-N, Total Phosphorus (TP) and COD by 75.9%, 68.4%, and 74.8%, respectively. Notably, Zn2+, Cu+, and Fe2+ were removed from wastewater with a ratio of 65.71%, 53.64%, and 58.89%, respectively. Biofilm attached cultivation of Chlorella Pyrenoidosa in swine wastewater containing heavy metals could accumulate considerable biomass and lipid, and the removal ratio of NH4+-N, TP, COD and, as well as heavy metal were high. Treatment of wastewater with biofilm attached cultivation showed an increasingly popular for the concentration of microalgae and environmental sustainability.